2015
DOI: 10.1111/hsc.12284
|View full text |Cite
|
Sign up to set email alerts
|

Promoting social capital to alleviate loneliness and improve health among older people in Spain

Abstract: Loneliness is especially frequent among older people in Southern Europe. Furthermore, promoting social capital to tackle loneliness and its health effects is an understudied intervention strategy. Therefore, a complex intervention was piloted in Spain in a pre-post study with a 2-year follow-up. Its aims were to explore the feasibility of the intervention and its short- and long-term effects. It was conducted in one mixed rural-urban and two urban areas of diverse socioeconomic levels from 2011 to 2012. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
147
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(165 citation statements)
references
References 64 publications
14
147
1
3
Order By: Relevance
“…[12][13][14] Their approaches (group-based support programs, 12 volunteer programs 13 and health promotion programs 14 ) are considerably different from the present study (event-based program using the resources of a university). This shows that community interventions using the resources of a university could strengthen older adults' neighborhood social networks.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Their approaches (group-based support programs, 12 volunteer programs 13 and health promotion programs 14 ) are considerably different from the present study (event-based program using the resources of a university). This shows that community interventions using the resources of a university could strengthen older adults' neighborhood social networks.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, social capital is operationally defined in more structural terms. Various studies have reported that social capital significantly influences psychological health, including loneliness (Coll-Planas et al, 2017;Nyqvist, Victor, Forsman, & Cattan, 2016) and depression (Haines, Beggs, & Hurlbert, 2011;Han & Lee, 2015).…”
Section: Social Capital Ptg Loneliness and Depressionmentioning
confidence: 99%
“…Systematic reviews, however, reveal an inconclusive evidence base in terms of the effectiveness of loneliness interventions, indicating that theoretically informed, group-based interventions which harness community resources yield the most promising results. This resonates with Coll-Planas et al's 14 theory-driven work that promotes the use of social capital to alleviate loneliness among older people.…”
Section: Introductionmentioning
confidence: 56%